Ionic Conduction Study Of 2-Hydroxyethyl Cellulose Doped With Dodecyltrimethyl Ammonium Bromide Solid Biopolymer Electrolytes - Nur Yasmin Abu Bakar; Mohd Ikmar Nizam Mohamad Isa (Penerbit UMT, 2024)
Green materials of the future 2 – Hydroxyethyl cellulose (2-HEC) doped with dodecyltrimethyl ammonium bromide (DTAB) have been prepared via solution cast technique. The typical XRD pattern shows this complexation has taken place in the amorphous phase. The system with 9wt. % DTAB presented the highest conductivity at room temperature, 2.80 x 10-5 S cm-1 and ionic conductivity was observed to be influenced by the DTAB concentration. It was found that the conductivity measurement at elevated temperatures follow Arrhenius model and dielectric values were found to increase with increasing temperature, thus indicating the green solid biopolymer electrolytes (SBEs) system to be a non–Debye type. Jonscher’s universal power law was employed to obtain the exponent s values. The results imply that the conduction mechanism in the most conductive green SBEs system can be represented by small polaron hopping (SPH) model.